2021
DOI: 10.3389/fphar.2021.648506
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Cell-Based Therapies in Chronic Lung Diseases: What About Asthma?

Abstract: Asthma is a widespread disease characterized by chronic airway inflammation. It causes substantial disability, impaired quality of life, and avoidable deaths around the world. The main treatment for asthmatic patients is the administration of corticosteroids, which improves the quality of life; however, prolonged use of corticosteroids interferes with extracellular matrix elements. Therefore, cell-based therapies are emerging as a novel therapeutic contribution to tissue regeneration for lung diseases. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 61 publications
0
1
0
Order By: Relevance
“…An increasing amount of evidence showed that exogenous mesenchymal stem cells (MSCs) effectively elicited inhibitory effects on airway inflammation and airway remodeling in asthmatic mice through the secretion of paracrine factors ( 5 , 6 ). Extracellular vesicles (EVs) are nano-scale membrane vesicles released by almost all cell types ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing amount of evidence showed that exogenous mesenchymal stem cells (MSCs) effectively elicited inhibitory effects on airway inflammation and airway remodeling in asthmatic mice through the secretion of paracrine factors ( 5 , 6 ). Extracellular vesicles (EVs) are nano-scale membrane vesicles released by almost all cell types ( 7 ).…”
Section: Introductionmentioning
confidence: 99%